(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Saani Kayidham is a 2022 Tamil -language crime action film which pivots around the life of Ponni, a hardworking police constable who seeks vengeance for the injustice she and her family face only due to the reason of belonging to a lower caste. The film was directed by Arun Matheswaran and actress Keerthi Suresh plays the role of Ponni. Ponni and her family always faces the atrocities of the people belonging to the upper caste community. Ponni always turns a blind eye towards all the misconducts of these high caste people until she gets sexually assaulted by them for a fight they had with her husband Maari, in the name of conducting elections. After that incident to avoid any kind of further trouble these men ruthlessly set fire to Ponni’s house when her husband Maari and her daughter Dhana are sleeping inside the house. The movie is analysed from the perspective of feminist criminology, a school of study which developed in the late1960s.